Correlation of plasma D-dimer levels with breast carcinoma - Halugodu, Amruthavarshini Satish; Sharma, Vidhyasagar M. (International Surgery Journal, 2021)
Background: Breast cancer is the most commonly occurring cancer in women. There is a correlation between cancer and hyper coagulation. Carcinoma increases the level of cross-linked fibrin degradation product (plasma D-dimer), indicative of systemic activation of fibrinolysis, hemostasis and angiogenesis. This study attempted to correlate raised plasma D-dimer in breast cancer. Methods: A retrospective study was conducted in the department of general surgery in GCS hospital, Ahmedabad where in patients admitted and treated for breast cancer between July 2020 to June 2021 were selected. Plasma D-dimer levels were correlated with final histopathological examination of breast specimen. Results: Plasma D-dimer levels were increased with advancing stage of disease, lymph node involvement and lymphovascular invasion. There was no significant relationship with increase in tumour size and histopathological grade of tumour. Conclusions: Plasma D-dimer levels are elevated in breast cancer, especially with advanced stage. It is an important marker of clinical stage, lymphovascular invasion, lymph node involvement. However it does not correlate with tumour size and histological grade. So pre- operative plasma D-dimer level is a safe, cost effective and convenient method for prediction of advanced stage in breast cancer.